Preliminary investigation on enzymatic activity in saliva of Hystrix cristata L., 1758. Issue 2 (19th July 2021) - Coppola, Francesca; Sagona, Simona; Betti, Laura; Palego, Lionella; Casini, Lucia; Giannaccini, Gino; Felicioli, Antonio
Abstract: Mammal's saliva contains a variety of electrolytes and proteins. They carry out an important role in the digestion process, in the antibacterial and antiviral activity, in lubrication and maintenance of oral general health status. It may also contain several enzymes according to dietary habits and general wellness. Sialochemistry is a valid alternative to the haematochemical analysis for the evaluation of animal health and nutritional status. At present, very little knowledge is available on health status and pathology of crested porcupine ( Hystrix cristata ) and no data are yet available on salivary enzymes. Between 2018 and 2020, a preliminary investigation of enzymatic activity on saliva samples was carried out from captured porcupines. In crested porcupine saliva, enzymatic activity of trypsin, chymotrypsin, N‐Aminopeptidase, amylase, lignin peroxidise, cellulase and chitinase were recorded. Superoxide dismutase, catalase, glutathione S‐transferase and alkaline phosphatase activity was also detected. The superoxide dismutase activity resulted higher (3.13 SD 3.58 U/mg proteins) than those of catalase (130.80 SD 110.65 mU/mg proteins) and glutathione S‐transferase (20.21 SD 16.62 mM/mg proteins). Alkaline phosphatase activity resulted lower (5.91 SD 6.12 mU/mg proteins) than acidic phosphatase (19.00 SD 16.16 U/mg proteins) with the highest values of saliva alkaline phosphatases recorded in young individuals. These preliminary data bring new knowledge on crested porcupine saliva enzymes and may provide a useful tool for further investigation on the adaptive response of crested porcupine to different environmental condition and diet. Additional investigation concerning a possible alternative use of saliva enzymes as indicator of health and nutritional status of this rodent are desirable.